PENGGUNAAN LIMBAH MARMER SEBAGAI FILLER PENGGANTI PADA CAMPURAN LASTON LAPISAAN ANTARA (AC-BC ) - Makmun R. Razali (Universitas Bengkulu, 2019)
Gradation of aggregate used is laston with kind of a mixed layer between (AC-BC) guided by the specifications of hot mix asphalt Kimpraswil 2003. Infrastructure Layer Asphalt Concrete (laston) is layered on construction pekerasan road that serves as a protective construction have also taken into account underlying structural value a mixture of hot asphalt with aggregate gradation continuously. This study was to determine the use of waste as a substitute filler marble against karekttistik Marshall. From the results of this study are eligible specification marshall mixture so that the waste can be used as a filler marner replacement.